2002
DOI: 10.1038/sj.ijo.0802063
|View full text |Cite
|
Sign up to set email alerts
|

Managing obesity: a survey of attitudes and practices among Israeli primary care physicians

Abstract: OBJECTIVES:To document and assess Israeli family physicians' (FPs) knowledge, attitudes and practices regarding the management of overweight and obesity. METHODS: Anonymous questionnaires were completed by 510 family physicians (82% compliance rate). The questionnaires were distributed in various continuous medical education sites of FPs in Israel. The measures included attitudes to and resources of knowledge on weight management, views regarding the prescription of drugs, approaches to and strategies recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
3
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 22 publications
9
96
3
6
Order By: Relevance
“…This is in agreement with earlier studies carried out in South Africa, Israel and the United Kingdom. [20][21][22] South African women, especially in black populations, think that being overweight is "beautiful and attractive". Hence, the majority of overweight black women view themselves as being of normal weight, healthy or very healthy.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with earlier studies carried out in South Africa, Israel and the United Kingdom. [20][21][22] South African women, especially in black populations, think that being overweight is "beautiful and attractive". Hence, the majority of overweight black women view themselves as being of normal weight, healthy or very healthy.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that GPs are negative about their own role in obesity treatment which in part reflects the problematic nature of obesity management. For example, one study of Israeli GPs by Fogelman and colleagues (10) found that although GPs believed it was part of their role to advise obese patients on the health risks of obesity, the majority of doctors thought they had not made any difference in getting their patients to make long-term changes in lifestyle. Similarly, a Glasgow based study by Mercer and Tessier (11) reported that doctors generally had 'little enthusiasm for weight management'.…”
Section: Introductionmentioning
confidence: 99%
“…However, a study in 11 European countries showed that more than half of the family doctors were sceptical of helping patients to achieve or maintain normal weight (Brotons et al, 2005). In addition, another study showed that 73% of family doctors believe counselling on weight reduction is not easy (Fogelman et al, 2002). Table 9 Regression model for actual nutrition communication behaviour towards overweight of family doctors (n ¼ 267)…”
Section: Daily Topic In General Practicementioning
confidence: 99%
“…In the case of more complicated topics, family doctors should utilise the expertise of dieticians. Application of the Team Approach might be useful (Fogelman et al, 2002).…”
Section: Adaptation Of Style: Family Doctors As Chameleonsmentioning
confidence: 99%